1986
DOI: 10.1002/ar.1092160412
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of the junction of the outflow tract and great arteries in the embryonic human heart

Abstract: The factors which give rise to the normal relationship between the great arteries and their respective ventricles are unknown. The developmental anatomy of this region was studied by using frontal, sagittal, or transverse serial histologic sections of 17 normal human embryos of Carnegie stages 15-19 from the Carnegie Embryological Collection. Distances and angles between major anatomic landmarks were determined by using computer reconstructions of the serially sectioned embryos, three-dimensional analytic geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Indeed, previous studies on human embryos (Goor et al, 1972;Lomonico et al, 1986) and chick embryos (Dor and Corone, 1985;Thompson et al, 1987) suggested that the conotruncus undergoes this sort of rotation during its remodeling.…”
Section: Secondary Heart Fieldmentioning
confidence: 99%
“…Indeed, previous studies on human embryos (Goor et al, 1972;Lomonico et al, 1986) and chick embryos (Dor and Corone, 1985;Thompson et al, 1987) suggested that the conotruncus undergoes this sort of rotation during its remodeling.…”
Section: Secondary Heart Fieldmentioning
confidence: 99%
“…24 Computerization of distances and angles between major anatomical landmarks, in particular the axis of the semilunar valves, showed that the junction of the OFT and the great arteries undergoes a rapid rotation in a counterclockwise direction, facing downstream, between Carnegie stages 15 and 19. 24 In addition, the angle of the aortic to pulmonary valve axis, relative to the inferior surface of congenitally malformed hearts, suggested that TOF, DORV, and TGA may result from an arrested rotation of the outflow region at the base of the great arteries. 25,26 We now report a counterclockwise rotation of OFT myocardium in the mouse embryo and examine this phenomenon in mice with OFT defects.…”
mentioning
confidence: 99%
“…These observations suggest that during OFT development (1) cells from the SHF migrate rotationally in a counterclockwise direction towards the OFT (viewed from the apex), (2) myocardial progenitor cells from the AHF migrate to the ventral wall of the OFT in a non-rotational manner, and (3) heart progenitors in the SHF and AHF contribute to the formation of distinct conotruncal regions. A previous developmental anatomy study involving human embryos showed that the junction of the OFT and the great arteries undergoes rapid rotation between Carnegie stages 15 and 19 (Lomonico et al, 1986). Ward et al (2005) showed that the dye-labeled right side of the SHF migrates spirally to the left side of the OFT in chicks.…”
Section: Discussionmentioning
confidence: 95%